TADWĪN AL-QUR’ĀN: ANALISIS HISTORIS KODIFIKASI DI ERA KHULAFĀ’ AL-RĀSYIDĪN - Ammar, Ammar; Yeti Dahliana (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study discusses the process of tadwīn al-Qur’ān or the codification of the Qur’an during the era of the Khulafā’ al-Rāsyidīn as a monumental effort to preserve the purity of the revelation. The focus of the study is directed at two main phases: the compilation of the Qur’an during the caliphate of Abū Bakar al-Ṣiddīq, which was motivated by the deaths of many ḥuffāẓ (Qur’an memorizers) in the Battle of Yamāmah, and the codification and standardization of the muṣḥaf during the caliphate of ‘Uthmān ibn ‘Affān to prevent differences in qirā’āt (recitations) that had the potential to cause division among Muslims. The research method used is a qualitative approach with historical analysis, through a review of classical and modern literature related to the history of the compilation of the Qur’an. The results show that these codification initiatives not only played a role in preserving the authenticity of the Qur’anic text but also laid the foundation for the transmission of the standard muṣḥaf (muṣḥaf ‘Uthmānī) that is used to this day. Thus, the compilation of the Qur’an during the era of the Khulafā’ al-Rāsyidīn represents a crucial historical milestone in Islamic civilization, ensuring the continuity, unity, and validity of the Divine revelation throughout the ages.